ASSOCIATIVE RINGS SOLVED AS LIE RINGS - M. B. Smirnov (Наука и техника)
The paper has proved that an associative ring which is solvable of a n- class as a Lie ring has a nilpotent ideal of the nilpotent class not more than 3×10n–2  and a corresponding quotient ring satisfies an identity [[x1, x2, [x3, x4]], x5] = 0.